Falling in Love With Work: The Effect of Enterprise Social Media on Thriving at Work - Liu, DongXu; Hou, Beigang; Liu, Yuanyuan; Liu, Pingqing (Frontiers in Psychology, 2021)
Using a survey of 300 employees in different types of enterprises and different positions, this study verified that the use of enterprise social media has a positive effect on employees’ work exuberance. The study separately examined the effects of social media applications for work tasks and for social tasks. Both types of applications had a positive impact on employees’ work exuberance. The study also identified the mediating role of challenge and obstructive stressors in this relationship. Work-related social media applications enhanced employees’ exuberance by reducing obstructive stressors, and social-related social media applications enhanced employees’ exuberance by reducing challenge stressors. The implications of these findings are that managers should pay attention to the use of enterprise social media, especially for social tasks, as this can enhance employees’ sense of exuberance.